Trend in Economic Performance and the Financial Flow into the Economic Sectors in Ethiopia during 2011-2020 - Tagese Helore Lamore (Contemporary Research in Business, Management and Economics Vol. 5, 2024)
This chapter attempted to analyse the trend in economic performance and the financial flow into the economic sectors in the country. Over the past ten years, the Ethiopian government has prioritized economic development and the reduction of poverty. The nation is among the poorest in sub-Saharan Africa, yet throughout the same decade, the government has released conflicting reports about its rapidly expanding economy—double digit and incremental growth, respectively. Developing countries are mainly marked by agricultural economies, where food self-sufficiency is always an issue. Poverty is a common phenomenon in these countries and economic dependency on developed countries is inevitable to escape poverty. On the one hand, government reports have indicated that the country is economically one of the fastest growing in Africa, a position that has been seconded by international financial institutions and other bilateral donors. On the other hand, the country remains on the list of poorest countries in the world. A qualitative approach was applied in analysing the reported data on economic performance in the country from 2011-2020. The GDP measure in Ethiopia during the past decade decreased from 11.39 in 2011 to 6.06 in 2020. The trend in specific economic sectors was decreasing with little progress in specific poverty indexes in the economic sector. There were marked inequalities between urban and rural areas in the country. The performance in water supply, electricity power provision and road networking in the country showed sluggish progress. The projected shift from an economy driven by agriculture to one driven by industry and services did not materialize. The nation kept depending on foreign aid to help reduce poverty, and throughout the last ten years, there has been a shifting trend in the amount of aid received. The study’s findings suggest that accurate reports on the nation’s economic success that use particular poverty indexes should be published. In order to attain goals for economic development and poverty reduction, it is also imperative that attention be paid to internal capabilities rather than depending too much on outside assistance.